Determination of the Energy Gap (Band Gap) of SiO2/ZnO using the Impregnation Synthesis Method - Imam Wahyudi Afrizon; Miftahul Khair (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
SiO2/ZnO synthesis by wet impregnation method has been successfully carried out which aims to determine the optimum band gap value of SiO2/ZnO. Characterization of the optical properties of SiO2/ZnO using a UV-Drs spectrophotometer which was measured in the wavelength range of 185 – 1100 nm. Characterization results obtained in the form of absorbance values and band gap values of SiO2/ZnO nanoparticles. From this study, the absorbance values of ZnO nanoparticles were obtained at wavelengths of 330 and 335 nm. After obtaining the absorbance values, the band gap values for ZnO and SiO2/ZnO nanoparticles were analyzed, which were 3.37 eV and 3.19 eV, respectively. The decrease in the value of the band gap in ZnO is due to the presence of SiO2 dopants in ZnO which will cause the formation of a new energy band between the valence band and conduction band so as to reduce the Energy Gap (Eg).